Dampak Pariwisata dalam Mewujudkan Kesejahteraan Masyarakat di Desa Wisata Karangrejo melalui Community Based Tourism (CBT) - El Yamin, Dioda Ashaab; Noor S., Fathia Salma Jihan; Salsabila, Idelia; Khairani, Jihan Nisrina; Putri, Nandita Arfiliana; Pratiwi, Ninda Ayu (Pusat Studi Pariwisata Universitas Gadjah Mada, 2024)
Community-based Tourism (CBT) is one of the concepts of tourism development through the role of local communities that is increasingly being developed in various specific tourist destinations. This study aims to explore the impact of tourism on the economic sector in realizing community welfare in Karangrejo Tourism Village, Borobudur District, Magelang Regency, through the role of CBT. In the process of managing and strategic tourism governance, Karangrejo Village has succeeded in implementing a fairly innovative and sustainable tourism base to be able to feel the positive impact of realizing the independence of the tourist village. The descriptive phenomenological approach was carried out through observation, interviews, and various documentation. The results show that the CBT strategy produces: (1) new business opportunities; (2) improving community skills; (3) opening access to a wider market; and (4) in the context of income, it is able to improve the welfare of the community involved by reducing poverty rates. In line with this, CBT is also able to encourage the preservation of culture and the environment to become an identity and strengthen the attraction in Karangrejo Tourism Village. Therefore, the active role and willingness of the local community to utilize the potential of Karangrejo Village has opened up broad economic opportunities so as to encourage the creation of sustainable local economic stability.